AN ECONOMICAL EVALUATION OF GAS ALLOCATION OPTIMIZATION FOR LNG AND POWER PLANT UTILIZATION IN: S GAS BLOCK CASE IN SULAWESI - Hafidz Mulky, Torikh
Natural gas production is usually sold to many industries, namely Power Plants and Mini LNG Plant. The economical evaluation of gas production is usually quantified namely Net Present Value (NPV). The economics of the upstream sector of gas production itself depends on several factors, including fiscal system, production rate, prices, operating cost and capital investment. Downstream sectors economics also depends on several factors and will be explained later in this study. In this study, economic evaluation for Sulawesi gas block was conducted to evaluate the economics of upstream sector for gas production using Gross Split Scheme by looking at the NPV result and also sensitivity analysis is conducted to determine what parameter that most affecting the NPV result. Then the economic analysis using NPV methods in the downstream sector is carried out to achieve maximum NPV value for the contractor based on the optimum allocation of gas production for Power Plant and Mini LNG Plant. The economic evaluation of upstream sector for Sulawesi gas block using Gross Split scheme is produces the NPV value of US$ 212,887,930, while most affecting parameter on this NPV result is gas price. The downstream sector economic analysis of gas production results shows that the optimum allocation of gas production for Power Plant is 47 % and for Mini LNG Plant is 53 % results in an NPV of US$ 340,793,000. The NPV results of upstream and downstream sectors indicates that this project is profitable if the contractor wants to expand the business of gas production to a downstream sector. The novelty of this study is to evaluate the economics of upstream sector using Gross Split scheme and to find the optimum gas utilization based on the shared of gas used in downstream sectors, namely Power Plants and Mini LNG Plant. Keywords: NPV, Power Plant, Mini LNG Plant,